A new method to rank fuzzy numbers using Dempster–Shafer theory with fuzzy targets - Chai, Kok Chin; Tay, K.M; Lim, Chee Peng (Elsevier Inc., 2016)
In this paper, an extended ranking method for fuzzy numbers, which is a synthesis of fuzzy targets and the Dempster–Shafer Theory (DST) of evidence, is devised. The use of fuzzy targets to reflect human viewpoints in fuzzy ranking is not new. However, different fuzzy targets can lead to contradictory fuzzy ranking results; making it difficult to reach a final decision. In this paper, the results from different viewpoints are treated as different sources of evidence, and Murphy’s combination rule is used to aggregate the fuzzy rank- ing results. DST allows fuzzy numbers to be compared and ranked while preserving their uncertain and imprecise characteristics. In addition, a hybrid method consisting of fuzzy targets and DST with the Transferable Belief Model is formulated, which fulfils a number of important ordering properties. A series of empirical experiments with benchmark ex- amples has been conducted and the experimental results clearly indicate the usefulness of the proposed method.